Predictors and outcomes of behavioral engagement in the context of text comprehension: when quantity means quality - Bråten, Ivar; Latini, Natalia; Haverkamp, Ymkje E. (Reading & writing, 2022)
Using a path analytic approach with a sample of Norwegian undergraduate readers, we investigated the effects of behavioral engagement on text comprehension as reflected in students’ post-reading written reports on the topic in question. Results indicated that the behavioral engagement components of writing time and the length of the written responses had distinctive, unique effects on comprehension performance, and that behavioral engagement also mediated the effects of cognitive (prior knowledge, working memory) and motivational (intrinsic reading motivation) individual differences on comprehension performance. Prior knowledge about the topic affected comprehension performance directly as well as indirectly through behavioral engagement. The results highlight the importance of behavioral engagement in the context of written comprehension assessment, and both theoretical and educational implications of these results are discussed.